Comprehensive Analysis of CRISPR-Cas Systems and Their Influence on Antibiotic Resistance in Strains - Tina Fallah; Morvarid Shafiei (Bioinformatics and Biology Insights)
Salmonella enterica is a gram-negative bacterium that demonstrates a remarkable ability to acquire antibiotic resistance genes (ARGs). The role of the CRISPR-Cas system in influencing antibiotic resistance in S. enterica is still under investigation. This study explores the distribution and impact of CRISPR-Cas systems on antibiotic resistance by analyzing 316 S. enterica genomes. We conducted sequence alignments, phylogenetic analyses, and conservation studies on Cas genes, direct repeats (DRs), and leader sequences. Promoter predictions and RNA secondary structure analyses were also performed. ARGs were identified, and their correlation with Cas gene clusters was evaluated. Our findings revealed that 82.33% of strains possess complete CRISPR-Cas systems, while 17.66% have orphan CRISPRs. We identified 290 distinct DRs, most of which formed stable stem-loop structures, although no promoter regions were detected within the leader sequences. Most spacers were chromosome-targeting, with a smaller proportion homologous to phages and plasmids. Importantly, strains with complete CRISPR-Cas systems showed a higher incidence of ARGs compared with those with orphan or no CRISPR systems. Specifically, the incidence of ARGs was 54.3% higher in strains with complete CRISPR-Cas systems than in strains without CRISPR-Cas systems, and 15.1% higher than in strains with orphan CRISPRs. Spearman’s correlation analysis confirmed a statistically significant but weak correlation between the presence of Cas genes and the frequency of ARGs ( P -value = 3.892e–06). These results suggest that CRISPR-Cas systems may play a role in the acquisition of ARGs, potentially through mutations under antibiotic pressure. Future studies should investigate mutations, particularly in Cas3 —the signature protein of type I CRISPR-Cas systems. In addition, experimental validation, such as culturing S. enterica strains with complete CRISPR-Cas systems under different antibiotic conditions, followed by sequencing to assess the uptake or absence of newly acquired ARGs, would help clarify the potential role of CRISPR-Cas systems in bacterial adaptation to antimicrobial pressures.